2016
DOI: 10.1016/j.athoracsur.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Levels After Cardiac Surgical Procedures: Association With Postoperative Bleeding, Trigger Values, and Target Values

Abstract: These data confirm the independent role of fibrinogen levels as determinants of SB after cardiac surgical procedures and suggest adequate cutoff values and fibrinogen concentrate doses to prevent or treat SB. However, the identified trigger and target values should be confirmed in prospective series of patients undergoing fibrinogen supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
1
27
1
5
Order By: Relevance
“…On the other hand, a study of fibrinogen concentrate administration after complex cardiac surgery to patients with risk factors for transfusion whose fibrinogen concentrations appear, in most cases, to have been > 1.5 g.l −1 resulted in a reduction in blood component transfusion and postoperative bleeding . The same group, after a larger but retrospective study , proposed 1.15 g.l −1 as a trigger value for fibrinogen supplementation after cardiac surgery with a post‐treatment target value of 2.80 g.l −1 . In actively bleeding patients, these values were increased to 2.15 g.l −1 and 3.75 g.l −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study of fibrinogen concentrate administration after complex cardiac surgery to patients with risk factors for transfusion whose fibrinogen concentrations appear, in most cases, to have been > 1.5 g.l −1 resulted in a reduction in blood component transfusion and postoperative bleeding . The same group, after a larger but retrospective study , proposed 1.15 g.l −1 as a trigger value for fibrinogen supplementation after cardiac surgery with a post‐treatment target value of 2.80 g.l −1 . In actively bleeding patients, these values were increased to 2.15 g.l −1 and 3.75 g.l −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results reported by other authors [52,65] and the reason to set the cut-off value for fibrinogen/cryoprecipitate substitution to A5 FIB < 9 mm in the cardiovascular algorithm. Ranucci et al [66][67][68][69] demonstrated that fibrinogen substitution in cardiac surgery is very effective to stop bleeding in patients with hypofibrinogenemia but that a substitution higher than an A5 FIB of 16 mm (corresponding to a plasma fibrinogen concentration of about 3 g/L) does not show any further improvement. Therefore, the first target in our cardiovascular algorithm is an A5 FIB ≥ 12 mm (fibrinogen concentration ≥ 2.5 g/L) and the second target (if bleeding continues in complex cardiovascular surgery) is an A5 FIB ≥ 15 mm (fibrinogen concentration ≥ 3 g/L).…”
Section: Korean J Anesthesiolmentioning
confidence: 99%
“…Studies of the best combination of sensitivity and specificity, in order to define the postoperative fibrinogen level associated with bleeding, established cut‐off values ranging from 1.44 to 2.85 g.l −1 . Karkouti et al found in a predictive model for excessive postbypass bleeding a cut‐off value 2.0 g.l −1 (sensitivity 50%, specificity 60%), whereas Kindo et al reported similar data with a cut‐off value of 2.2 g.l −1 (sensitivity 67%, specificity 57%).…”
Section: Drug Efficacymentioning
confidence: 99%
“…Ranucci et al found that a postoperative fibrinogen level of 2.87 g.l −1 yielded a negative predictive value of 98%. Previous studies mainly aimed for a target fibrin‐based thromboelastometry assay of 22 mm , which roughly corresponds to a plasma level of 3.75 g.l −1 . However, this may be considered too high, as more recent studies confirmed 14 mm of maximum clot firmness in the fibrin‐based thromboelastometry assay, yielding a 98% negative predictive value for severe postoperative bleeding .…”
Section: Drug Efficacymentioning
confidence: 99%